EKONOMI POLITIK: RELASI PEMERINTAH DAERAH DAN MASYARAKAT DALAM KASUS PERTAMBANGAN EMAS TANPA IZIN DI DESA PETAPAHAN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI TAHUN 2013-2015 - Dona Fauziah; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Mining Without Permission (PETI) is a mining business done by an individual, group, or company in its operations did not have permission from the appropriate government agency regulations that apply. This study aims to determine the relationship and impact of the relationship between government and society daerag in illegal gold mining activities in the Village Petapahan District of Gunung Toar Regency Kuantan Singingi years 2013-2015.This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Relationship between local government and the community in illegal gold mining activities in the Village Petapahan District of Mount Toar Regency Kuantan Singingi years 2013-2015 seen the relationship between authorities and entrepreneurs in getting financial benefits on illegal gold mining activities. Authorities and entrepreneurs the main actors in illegal gold mining activities and involve several public figures who are considered able to provide comfort to the entrepreneur. Impact of relationships that occur very many negative than positive. Where the impact of illegal mining is very damaging to the environment, tantanan social culture, and also to the local government.Keywords: Relationships, Who Gets What, When, How